Avaliação da eficácia da pele de tilápia (Oreochromis niloticus) como xenoenxerto em úlceras cutâneas traumáticas em equinos - Costa, Behatriz Odebrecht (2023)
Horses are naturally prone to accidental injuries, which is one of the most common reasons they are examined by a veterinarian. In Brazil, biological substitutes for trauma injuries are rarely used due to their high cost, even though they offer more advantages for patients compared to traditional treatments. This context has driven research towards the development of new biomedical devices for clinical use, and tilapia skin has been studied as an alternative biomaterial. Based on the proven effectiveness of this biological dressing in healing burns in humans, the question arose about the benefits of its use in healing different types of wounds and in other species.Therefore, the aim of this study was to evaluate the effectiveness of using Nile tilapia skin as a xenograft in the management of traumatic ulcers in horses, compared to silver sulfadiazine dressing. Thirteen mixed-breed horses were selected from the equine herd of RPMONT/PMCE for this clinical study. Animals with traumatic wounds that met the inclusion criteria were randomly assigned to two treatment groups: Tilapia Skin and Silver Sulfadiazine. The following parameters were evaluated for each treatment group: variation in ulcer area measured at the end of treatment compared to pre-treatment measurement, time to complete healing, proportion of animals with complete ulcer healing during the follow-up period, number of dressing changes throughout the study, and histopathological analysis to assess the inflammatory process and collagen deposition.There were no statistically significant differences between the two groups in terms of the evaluated parameters, except for the number of dressings performed in each group. Therefore, it can be concluded that treatment with tilapia skin dressing in horses has a similar healing response to a market product known to have a favorable effect on healing, but with a significant decrease in the number of dressings required. This implies greater comfort and consequent improvement in the animal's well-being.